UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKN) DENGAN MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE NUMBERED HEADS TOGETHER (NHT) KELAS V-B SD BUDI MURNI 6 MEDAN TAHUN PEMBELAJARAN 2016-2017 - SITORUS, IMELDA J (Unversitas Katolik Santo Thomas, 2018)
This research was aimed to (1) Increasing the result of civic educationlesson by cooperative learning model numbered heads together (NHT) on studentat Fifth grade of SD Budi Murni 6 Medan academic year 2016-2017. (2)Describing problems that faced in applying of cooperative learning modelnumbered heads together (NHT) in order to increase the result of civic educationsubject. The subject that did this research was the researcher that collaboratedwith homeroom teacher as observer meanwhile the object of this research wasstudent at fifth grade of SD Budi Murni 6 Medan totally 37 students thatcontained 20 male and 17 female. The technique in colleting the data byobservation to the result of study test and activity of student‟s study. The result ofthe research showed the increase of result of student‟s study on civic educationsubject and the material mention organizations within the school and communityof on student at fifth grade of SD Budi Murni 6 Medan. This thing proved by theresult of research that was done on student‟s pretest and the student got maximumscore amount 6 students (16,21%) meanwhile student that had not been achievedamount 31 students (83,79%). So the next research was continued on cycle I thestudent that had been passed the maximum score was 15 students or 40,54%meanwhile student that had not been passed totally 22 students or 59,46%,, sothere was an increase on cycle I compared to pretest. But it had not beenappropriated the category of completion that had been determined. So it wascontinued by cycle II and the student got complete score totally 33 students or89,18% meanwhile student that had not been passed amount 4 students or10,82%, so there was an increase on cycle II compared to cycle I and it had beenfulfilled the completion that had been determined. Next on cycle I teacher didactivity and got averaging amount 60% and there was an increase to be 88% oncycle II. Meanwhile the activity of student on learning process got averagingamount 58% and there was an increase to be 92% on cycle II. By that mean theconclusion was got that by using cooperative learning model numbered headstogether (NHT) on civic education subject by material of mention organizationswithin the school and community at fifth grade SD Budi Murni 6 MedanAcademic Year 2016-2017 could be increase the result of student‟s study.Therefore it was suggested to use the cooperative learning model numbered headstogether (NHT) for the next study in order to increase the student‟s study.